Ground-Coupled Natural Circulating Devices (Thermosiphons): A Review of Modeling, Experimental and Development Studies - Messaoud Badache; Zine Aidoun; Parham Eslami-Nejad; Daniela Blessent (Inventions, 2019)
Compared to conventional ground heat exchangers that require a separate pump or othermechanical devices to circulate the heat transfer fluid, ground coupled thermosiphons or naturallycirculating ground heat exchangers do not require additional equipment for fluid circulation in theloop. This might lead to a better overall efficiency and much simpler operation. This paper providesa review of the current published literature on the different types of existing ground coupledthermosiphons for use in applications requiring moderate and low temperatures. Effort has beenfocused on their classification according to type, configurations, major designs, and chronologicalyear of apparition. Important technological findings and characteristics are provided in summarytables. Advances are identified in terms of the latest device developments and innovative conceptsof thermosiphon technology used for the heat transfer to and from the soil. Applications arepresented in a novel, well-defined classification in which major ground coupled thermosiphonapplications are categorized in terms of medium and low temperature technologies. Finally,performance evaluation is meticulously discussed in terms of modeling, simulations, parametric,and experimental studies.